2022
DOI: 10.1111/ene.15423
|View full text |Cite
|
Sign up to set email alerts
|

Risk of intracranial meningioma with three potent progestogens: A population‐based case–control study

Abstract: Background and purpose A dose‐dependent association between the use of cyproterone acetate (CPA) and intracranial meningioma has been identified but data for other potent progestogens are scarce. The association was assessed between intracranial meningioma surgery and exposure to three potent progestogens: CPA (≥25 mg/day), nomegestrol acetate (NOMAC) (3.75–5 mg/day) and chlormadinone acetate (CMA) (2–10 mg/day). Methods In this nationwide population‐based case–control study, cases underwent surgery for intrac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 35 publications
2
21
0
Order By: Relevance
“…Our study complements the previous large nationwide cohort study focusing on high dose CPA-associated meningiomas referred for neurosurgical resection or radiation [29]. Despite the small size of CMA and NA groups (with a single case of meningioma in each), the prevalence among CMA (1%) and NA (5%) users is consistent with a lower risk of meningioma under these drugs than in CPA users, as reported in the large epidemiological cohort focusing on surgically-treated meningioma [30].…”
Section: Discussionsupporting
confidence: 84%
See 3 more Smart Citations
“…Our study complements the previous large nationwide cohort study focusing on high dose CPA-associated meningiomas referred for neurosurgical resection or radiation [29]. Despite the small size of CMA and NA groups (with a single case of meningioma in each), the prevalence among CMA (1%) and NA (5%) users is consistent with a lower risk of meningioma under these drugs than in CPA users, as reported in the large epidemiological cohort focusing on surgically-treated meningioma [30].…”
Section: Discussionsupporting
confidence: 84%
“…The main strength of this study lies in its "real-life" approach. Indeed, numerous retrospective cohorts and one meta-analysis already established the link between progestins and meningioma [29][30][31]. However, the yield of MR screening proposed by the French authorities was unknown, especially regarding the expected detection rate, and imaging characteristics of uncovered meningioma in a pauci/asymptomatic population.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Data reviewed by PRAC included an observational cohort study and a case–control study that used information from the French national health system 3 4. The studies investigated high-dose nomegestrol used as monotherapy and found an increase in risk of meningioma associated with the cumulative dose and age of the patient 3.…”
Section: Overviewmentioning
confidence: 99%